NEW DIMENSIONS OF THE IMPORTANCE OF A CREATIVE WORK ENVIRONMENT AND ITS IMPACT ON THE MANAGEMENT OF CONTEMPORARY ORGANIZATIONS - Vukotić, Svetlana; Karabašević, Darjan; Mirčetić, Vuk; Maksimović, Mlađan (International Journal of Economic Practice and Policy, 2020)
A creative work environment has been attracting researchers’ attention in recent decades. Apart from the academic public, the professional public also shows an interest in this concept. It is already becoming a necessity nowadays. Because competition has intensified, the need to be different in the business process has been reinforced. Uniqueness is most pronounced in creativity. Not very often can creativity repeat itself in the same way. Modern management practice recommends that the inventiveness and creativity of all employees who represent partners in a creative work environment should be taken into account. This paper is aimed at analyzing the importance of generating a creative work environment and the implications for management in organizations. In addition to creativity, a team concept has been introduced into a creative work environment, as well as multitasking and the creative competence of employees as regards job designing. Leadership and communication in a creative work environment, and motivation and a reward for performance, are also discussed. A creative work environment is a very layered and complex concept with a challenging and stimulating effect on future research. A creative work environment is an essential prerequisite for achieving and maintaining a competitive advantage, while enabling the organization to follow its mission and vision.
Keywords: creativity; creative work environment; team work; job design; leadership; motivation; innovation